(untitled) (International Journal of Engineering and Computer Science, 2014)
Network survivability is the capacity of a network keeping connected under loss and intrusions, which is a major concern to the design and design interpretation of wireless ad hoc sensor networks. Ad-hoc low power wireless networks are in inquisition in both discerning and ubiquitous computing. The proposed method discusses about energy draining attacks at the routing protocol layer, which drains battery power. A innovative approach for routing protocols, affect from attack even those devised to be protected which is short of protection from these attacks, which we call energy debilitating attacks, which enduringly disable networks by quickly draining nodes battery power. These energy depletion attacks are not protocol specific but are disturbing and hard to notice, and are easy to carry out using as few as one malicious insider sending only protocol compliant messages.